Diagnóstico directo de hemotrópicos en el ganado bovino de la parroquia Eloy Alfaro del cantón Chone - Macías Bermeo, Edison Francisco (2022)
The objective of this research was to evaluate the prevalence of hemotropics in cattle farms of the Eloy Alfaro parish of the Chone canton. For this work, 285 blood samples were taken from nine cattle herds according to the type of conglomerate (large, medium and small). Statistical analysis was used as the percentage to measure the prevalence and the survey in Microsoft Excel (2016), minimum value, maximum value, mean, standard deviation, coefficient of variation and the value of Chi square with a significance level of 5% for measure the degree of association between variables and prevalence using the statistical package InfoStat version 2020. Diagnosis of Anaplasmosis and babesiosis was made by blood smear with Giemsa stain and trypanosomiasis through Woo's test. A prevalence of 21.05% was obtained for Anaplasma marginale, 0% for Babesia spp and Trypanosomas spp; of which (11.58%) corresponds to a large property and (9.47%) to a medium property. It was found that there are significant differences (P<0.05) between the variable sex-age; likewise, a correlation between Anaplasma marginale and the clinical aspects of hematocrit, total proteins and temperature (P<0.01) was evidenced. It is concluded that there is a prevalence of Anaplasma marginale in cattle farms of the Eloy Alfaro parish; it is due to the presence of ticks in the summer season, the owners' lack of knowledge about hemotropics, poor sanitary management of manure and iatrogenic transmission through sharp objects with infected blood.